Evaluation Of The Legal Framework For Promoting Sustainable Development In The Extractive Host Communities In Nigeria - Ihugba, Bethel Uzoma; Okoro, Sergius Nnamdi (Journal of Sustainable Development Law and Policy, 2025)
The extraction of oil and mineral wealth has some environmental, social, economic and political impact on the host communities. In many instances these communities do not derive any sustainable developmental benefit from the wealth extraction activities in their area and where they do, it is less than the magnitude of harm suffered. This has contributed to conflicts between government and host communities, and between host communities and mining companies. This suggests that either there is no legal framework for extractive industry host community development or they are weak or not applied. In Nigeria, existing legal framework includes revenue allocation formulas between the Federal and State Governments, the establishment of bodies like the Niger Delta Development Commission, and enactment of laws like the Nigeria Minerals and Mining Act (NMMA) 2007, the Nigeria Extractive Industry Transparency Initiative (NEITI) Act 2007 and the proposal of the Petroleum Industry Bill 2012 and the recently passed Petroleum Industry Governance Bill 2016. However, despite this framework, contentions persist and there is sparse evidence of sustainable development in host communities to counter some conclusions of ineffectiveness. This article, therefore, examines some of the legal framework to determine their contribution or otherwise and potential towards sustainable host community development.